Agastya : Improving Critical Thinking and Leadership Skills - Tinsley, Elaine A.; Navarrete Moreno, Cristina (World Bank, Washington, DC, 2017)
Many of India’s disadvantaged youth are apathetic about their education from the formal schooling system, resulting in high dropout rates. Lack of interest and perceived value of education often cause low retention and dismal learning outcomes, which can perpetuate poverty and contribute to the socio-economic divide. In India, however, creative learning is a privilege of the rich few. To remedy this situation, Agastya operates a hands-on science education program, equipping disadvantaged students of government schools in rural areas with tools and learning that foster confidence, creativity, teamwork, and leadership. Agastya’s learning methods take the form of activity - project and demo-based learning, peer-to-peer learning, and learning from nature. Agastya uses a variety of delivery channels: science center’s serve as a hub for activities in a region, teacher trainings, science fairs, and summer camps; mobile science labs and lab-in-a-box programs deliver education to students’ doorsteps and classrooms; government schoolteachers receive training in creative learning methods; and selected students obtain additional education on scientific concepts to become peer instructors.